Analysis of Implementation Professionalism, Professional Ethics, Auditor Experience, and Independence as A Materiality Level Consideration in KAP Of Palembang City - Leriza Desitama Anggraini; Melinda (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This research aims to determine the extent of the implementation of professionalism, professional ethics, auditor experience, and independence to consider the level of materiality at the Public Accountant Office in Palembang. Samples were selected using non-probability techniques. Data for 47 respondents were collected through observation and questionnaires. This study implements multiple linear regression methods to analyze data. The analysis results prove that partially each of the factors of professionalism, professional ethics, auditor experience, and independence have a significant effect on the consideration of the level of materiality. On the other hand, partially the auditor's knowledge does not significantly affect materiality level considerations. Simultaneously, professionalism, professional ethics, auditor experience, and independence significantly affect the reflection of materiality.